STUDY THE EFFECT OF PACKAGING MATERIALS AND STORAGE PERIOD ON RHEOLOGICAL PROPERTIES OF FLOUR - S. AL-Jbory (Mesopotamia Journal of Agriculture)
The effect of packaging materials and storage period on rheological properties of wheat flour was studied. wheat flour was packed in polypropylene and paper sacks and stored at30Cº for 30, 60, 90 days. Results of amylograbh show that there were no significant (P<0.05) differences between initial temperature of gelatinization of flour suspension in all storage conditions. Results of farinograph show that a significant (P<0.05) increase in the amount of absorption water by flour stored in polypropylene, whereas there was a significant increase in the same parameter for flour stored in paper sacks for 90 days. Results also show that there were significant (p<0.05) differences between dough time for control flour and other samples stored in all storage conditions. The dough time was decreased and dough ripping time increased with increasing storage period, whereas dough stability time was increased with increasing storage period and critical dough coefficient was decreased with increasing storage period. The results of extensograph show that decreasing the elasticity values and increasing the elasticity resistance of flour packed in both containers with increasing storage period. This was resulted in increasing the ratio of elasticity resistance/elasticity value and increased the energy for 90 days storage period in both containers. Generally, changes in the rheological properties of the flour stored in paper sacks were less than that of stored in polypropylene sacks and there was no indication for insects infection in the flour.